The Impact of Artificial Intelligence on Mathematics Education: A Systematic Literature Review - Azmi, Nur (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study evaluates the impact of Artificial Intelligence (AI) in mathematics education through a systematic literature review. Thirty studies published between 2020 and 2026 were analyzed to identify types of AI used, educational contexts, mathematical concepts addressed, research methods, as well as student learning outcomes and teacher practices. Results indicate that AI including intelligent tutoring systems, adaptive learning platforms, AI chatbots, generative visualization tools, and learning analytics dashboards enhances student performance, engagement, and perception in mathematics. The studies also highlight the importance of teacher readiness, digital literacy, and infrastructure support for effective AI integration. Limitations such as small sample sizes and short intervention durations suggest areas for future research. These findings provide comprehensive insights into the role of AI in mathematics education and practical implications for pedagogy and research.